Laki laki Pemanfaaatan sampah anorganik sebagai alternatif terbarukan pembangkit listrik tenaga uap kabupaten bengkulu utara: Pemanfaaatan sampah anorganik sebagai alternatif terbarukan pembangkit listrik tenaga uap kabupaten bengkulu utara - M Habibur Rohman - (Institut Riset dan Publikasi Indonesia, 2025)
The increase of inorganic waste in Bengkulu Province has led to environmental pollution and landfill accumulation. To address this issue, this study analyzes the potential of utilizing inorganic waste as a renewable energy source through a Steam Power Plant (PLTU) system. The method includes observation and quantitative analysis of waste volume and its energy potential. Results indicate that the combined average waste from Bengkulu Province and North Bengkulu reaches 10,266.5 tons/day. Energy calculations show that waste combustion can generate 131.7 MWh of electricity per year and a daily power output of 15.03 MW. These findings demonstrate that inorganic waste has significant potential as an alternative fuel for steam power plants and can help reduce waste volume while supplying renewable electricity for the Bengkulu region.